OTX2 stimulates adult retinal ganglion cell regeneration - Raoul Torero Ibad; Nicole Quenech’du; Alain Prochiantz; Kenneth L Moya (Neural Regeneration Research, 2022)
Retinal ganglion cell (RGC) axons provide the only link between the light sensitive and photon transducing neural retina and visual centers of the brain. RGC axon degeneration occurs in a number of blinding diseases and the ability to stimulate axon regeneration from surviving ganglion cells could provide the anatomic substrate for restoration of vision. OTX2 is a homeoprotein transcription factor expressed in the retina and previous studies showed that, in response to stress, exogenous OTX2 increases the in vitro and in vivo survival of RGCs. Here we examined and quantified the effects of OTX2 on adult RGC axon regeneration in vitro and in vivo. The results show that exogenous OTX2 stimulates the regrowth of axons from RGCs in cultures of dissociated adult retinal cells and from explants of adult retinal tissue and that RGCs respond directly to OTX2 as regrowth is observed in cultures of purified adult rat RGCs. Importantly, after nerve crush in vivo, we observed a positive effect of OTX2 on the number of regenerating axons up to the optic chiasm within 14 days post crush and a very modest level of acuity absent in control mice. The effect of OTX2 on RGC survival and regeneration is of potential interest for degenerative diseases affecting this cell type. All animal procedures were approved by the local “Comié d’éιthique en expérimentation animale n°59” and authorization n° 00702.01 delivered March 28, 2014 by the French “Ministére de l’enseignement supérieur et de la recherche”.